Patterns of mental health problems and resilience among immigrant and refugee adolescents: a latent profile analysis - Aalto, Sanni; Punamäki, Raija-Leena; Vänskä, Mervi; Kankaanpää, Reeta; Turunen, Tiina; Lahtinen, Oskari; Derluyn, Ilse; Spaas, Caroline; De Haene, Lucia; Smith Jervelund, Signe; Skovdal, Morten; Andersen, Arnfinn J.; et al. (Informa UK Limited, 2025)
Background: Immigrant and refugee adolescents often face traumatic experiences and are vulnerable to mental health problems, such as post-traumatic stress disorder (PTSD), anxiety and depression. Yet, they also show remarkable resilience in the face of these stressors. Research is still scarce on how both mental health problems and resilience dynamically interplay in immigrant and refugee adolescents' development.
Objective: We aimed to identify latent profiles of immigrant and refugee adolescents' wellbeing, consisting of externalizing and internalizing symptoms, PTSD (intrusion and avoidance), and resilience, and analyse the demographic and contextual determinants of these profiles.
Method: We employed cross-sectional survey data from the RefugeesWellSchool project for 1607 immigrant and refugee adolescents (mean age 15.3 years, SD 2.15, 42.3% girls) from six European countries: Belgium, Denmark, Finland, Norway, Sweden, and the United Kingdom. Latent profile analysis and three-step procedure with BCH weights were used to identify the wellbeing profiles and their determinants.
Results: Results identified four adolescent wellbeing profiles: (1) Low symptoms (49.7%, n = 791); (2) High symptoms with intrusion (10.6%, n = 169); (3) Moderate symptoms (26.9%, n = 428); and (4) Resilient avoidant (12.8%, n = 203). Older participants, those with refugee background, shorter residence in the host country, more experiences of daily stressors or discrimination, or low family support were less likely to belong to the Low symptoms or Resilient avoidant groups (p <= .001).
Conclusions: The profiles reflected distinct differentiation of intrusive and avoidance dimensions of the PTSD-symptoms. Intrusion clustered with high level of other mental health problems, whereas avoidance co-occurred with high resilience. Experiences related to immigration, stressors, and family support were crucial determinants of the wellbeing profile membership. Future interventions should utilize information obtained by person-centered studies to create better targeted and tailored support for immigrant and refugee adolescents.